MUCOGINGIVAL PARAMETERS OF MAXILLARY ANTERIOR TEETH IN PERUVIAN DENTAL STUDENTS: A CROSS-SECTIONAL STUDY - Jiménez Fabián, Elizabeth Kalett (2025)
Objective: To determine the mucogingival parameters of the maxillary anterior teeth in Peruvian dental students, including the width of keratinized gingiva, gingival phenotype, interdental papilla height, and gingival zenith position. Materials and Methods: A cross-sectional study was conducted among 128 randomly selected dental students from a private university in Lima, Peru. Prior to data collection, a pilot study and examiner calibration were performed. Mucogingival parameters were clinically assessed using a North Carolina periodontal probe. Measurements were analyzed by tooth type, sex, and age using the Chi-square test, Mann–Whitney U test, Friedman test, and Dunn’s post hoc test (α = 0.05). Results: The mean width of keratinized gingiva ranged from 4.99 mm to 5.29 mm, and the height of the interdental papilla ranged from 3.99 mm to 4.41 mm. A thick gingival phenotype was observed in 83.6% of participants. Gingival zenith deviation from the midline ranged from 0.15 mm to 0.18 mm. No statistically significant differences in mucogingival parameters were found by sex or age. Conclusion: Mucogingival parameters showed notable individual variability among young Peruvian dental students, with no significant influence of sex or age. These values may serve as clinical reference points for periodontal assessment in the esthetic zone. Clinical relevance highlighted that population-specific data on mucogingival characteristics can improve diagnostic accuracy and support personalized treatment planning. These findings contribute to clinical decision-making and future research in periodontology and esthetic dentistry.